2009
DOI: 10.1186/1757-1626-2-98
|View full text |Cite
|
Sign up to set email alerts
|

Hughes-Stovin Syndrome: a case report and review of the literature

Abstract: BackgroundHughes-Stovin syndrome is a rare entity. The aetiology of Hughes-Stovin syndrome is still unknown and the natural course of the illness is usually fatal; however it is supposed to be a clinical variant manifestation of Behçet disease.Case presentationWe report the case of an 18 years old, greek male patient with Hughes-Stovin syndrome, who initially presented with deep vein thrombosis. There were no findings consistent with Behçet disease and the haemoptysis was treated successfully with methylpredni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 15 publications
0
51
0
2
Order By: Relevance
“…Five case reports, each describing the case of one patient, diagnosed Hughes-Stovin syndrome. 37 21,27,57,81,113,118 and persistent in 2 (11.8%) patients. 18,63 Additionally, one patient was described as having hemoptysis of unknown origin on admission.…”
Section: Resultsmentioning
confidence: 99%
“…Five case reports, each describing the case of one patient, diagnosed Hughes-Stovin syndrome. 37 21,27,57,81,113,118 and persistent in 2 (11.8%) patients. 18,63 Additionally, one patient was described as having hemoptysis of unknown origin on admission.…”
Section: Resultsmentioning
confidence: 99%
“…18 In addition, the Hughes-Stovin syndrome, a rare autoimmune disorder of unknown origin that generally affects young adult men, is also characterized by PAA formation, recurrent thrombophlebitis, and a high risk of PAA rupture. 19 However, some authors have suggested that the Hughes-Stovin syndrome is a cardiovascular manifestation of the Behçet syndrome and therefore part of the same disease process. 18,19 PA hypertension (PAH) is an important cause of PAA formation 10,14,20 and has been suggested to be a clinical symptom of an existing PAA.…”
Section: Acquired Causesmentioning
confidence: 99%
“…The distribution of the vascular component of the syndrome is as follows: arterial (7%), venous (25%) or both (68%) [14]. Some authors have proposed that HSS may actually be a partially manifested Behçet's disease (BD) based on their similar findings [12,15,16]. In fact, HSS and BD are the only vasculitides associated with the development of pulmonary artery aneurysms yet most HSS patients do not have typical manifestations of BD such as oral and genital ulcers, uveitis or arthralgia.…”
Section: Discussionmentioning
confidence: 97%